A simple model of salt crystal formation in an evaporating liquid film; International Journal of Heat and Mass Transfer; Vol. 256 - Misyura S. Ya. Sergey Yakovlevich; Antonov D. V. Dmitry Vladimirovich; Mikulich A. V. Anastasiya Vyacheslavovna; Strizhak P. A. Pavel Alexandrovich; Morozov V. S. Vladimir Sergeevich; Sazhin S. S. Sergey Stepanovich (2026, 2026)
Title screen